2011
DOI: 10.1021/bi101932s
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of 4′-Phosphopantetheine - GmACP3 fromGeobacter metallireducens: A Specialized Acyl Carrier Protein with Atypical Structural Features and a Putative Role in Lipopolysaccharide Biosynthesis

Abstract: GmACP3 from Geobacter metallireducens is a specialized acyl carrier protein (ACP) whose gene, gmet_2339, is located near genes encoding many proteins involved in lipopolysaccharide (LPS) biosynthesis, indicating a likely function for GmACP3 in LPS production. By overexpression in Escherichia coli, about 50% holo-GmACP3 and 50% apo-GmACP3 were obtained. ApoGmACP3 exhibited slow precipitation and non-monomeric behavior by 15 N NMR relaxation measurements. Addition of 4′-phosphopantetheine (4′-PP) via enzymatic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 75 publications
2
27
0
Order By: Relevance
“…The IR data were entirely consistent with this hypothesis: the CN stretching band for cyanylated GmACP3 is red-shifted by 6–7 cm –1 compared to the cyanylated ACT ACP (Figure 2 ), in agreement with previous findings that the Ppant arms of these two proteins are in markedly different environments 11 , 31 and confirming that the Ppant* can serve as a site-specific reporter of the Ppant arm’s local environment.…”
supporting
confidence: 90%
“…The IR data were entirely consistent with this hypothesis: the CN stretching band for cyanylated GmACP3 is red-shifted by 6–7 cm –1 compared to the cyanylated ACT ACP (Figure 2 ), in agreement with previous findings that the Ppant arms of these two proteins are in markedly different environments 11 , 31 and confirming that the Ppant* can serve as a site-specific reporter of the Ppant arm’s local environment.…”
supporting
confidence: 90%
“…Unusually, the terminal thiol of the 4 0 -PP of GmACP3 interacts with a conserved, hydrogen bonded Trp-His pair at the entrance to a hydrophobic cavity. 53 As well as the assignment of unambiguous NOEs between the body of the ACP and the 4 0 -PP group, NMR relaxation studies showed that the amide groups of the 4 0 -PP side arm were rigid and not mobile as observed in other holo-ACPs (Fig. 3F).…”
Section: Structures 21 Type II Acp Structuresmentioning
confidence: 68%
“…The Ppant arms of holo ACP species adopt a spectrum of dynamic states, ranging from tightly bound to the carrier protein surface to freely swinging. For example, the prosthetic group of the holo form of an atypical Geobacter metallireducens ACP ( Gm ACP 3 ) is rigid, displaying S 2 order parameter values similar to those for structured backbone sites (∼0.8), together with 23 Ppant-protein NOE connections [ 51 ]. The Plasmodium falciparum type II FAS ACP ( Pf ACP) represents the centre ground, exhibiting two conformers in slow exchange due to different docked orientations of the Ppant moiety; in both states the prosthetic group is semi-rigid, with S 2 values for N 4 and N 8 in the 0.1–0.5 range, but also 6 NOEs between the arm and the protein surface [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, backbone 1 H N / 15 N chemical shift perturbations appear to be less sensitive probes of protein/prosthetic group interactions than Ppant 15 N relaxation parameter measurements or the detection of direct Ppant-protein NOE connections. For mACP 9 , which possesses a highly dynamic arm, the largest detected Δδ av value between the apo and holo forms is ∼0.3 ppm ( Figure 4 A), whereas the largest corresponding shift change for the firmly bound Gm ACP 3 species is only ∼0.4 ppm [ 51 ]. Furthermore, we found that the magnitude of shift changes between apo and holo mACP 9 did not depend in a straightforward way on distance from the point of attachment of the prosthetic group.…”
Section: Discussionmentioning
confidence: 99%